2012
DOI: 10.1002/hep.24709
|View full text |Cite
|
Sign up to set email alerts
|

Translationally Controlled Tumor Protein Induces Mitotic Defects and Chromosome Missegregation in Hepatocellular Carcinoma Development

Abstract: Emerging evidence implicates the chromodomain helicase/ATPase DNA binding protein 1-like gene (CHD1L) as a specific oncogene in human hepatocellular carcinoma (HCC). To better understand the molecular mechanisms underlying HCC cases carrying CHD1L amplification (>50% HCCs), we identified a CHD1L target, translationally controlled tumor protein (TCTP), and investigated its role in HCC progression. Here, we report that CHD1L protein directly binds to the promoter region (nt 2733 to 21,027) of TCTP and activates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 31 publications
5
73
0
Order By: Relevance
“…TCTP was overexpressed in many human cancer tissues including liver (42), colorectal (43), prostate (44), breast (45), and lung cancer (46). Similarly, TCTP was detected in pancreatic cancer cell lines, and malignant duct epithelial cells and some normal acinar cells but not normal pancreatic duct epithelial cells adjacent to tumor foci.…”
Section: Discussionmentioning
confidence: 99%
“…TCTP was overexpressed in many human cancer tissues including liver (42), colorectal (43), prostate (44), breast (45), and lung cancer (46). Similarly, TCTP was detected in pancreatic cancer cell lines, and malignant duct epithelial cells and some normal acinar cells but not normal pancreatic duct epithelial cells adjacent to tumor foci.…”
Section: Discussionmentioning
confidence: 99%
“…Promotion of mitosis. A very specific role of TCTP in cancer promotion was described by Chan et al in 2012, who studied the chromodomain helicase/ ATPase DNA-binding protein 1-like gene (CHD1L), which is a specific oncogene in human hepatocellular carcinoma (HCC) (Chan et al 2012b). They found that CHD1L acts as a transcriptional activator of TCTP and that the resulting overexpression of TCTP contributed to the mitotic defects of tumour cells.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 99%
“…For example, TCTP promoted cell cycle progression in pancreatic cancer cells through stabilisation of the protein kinase Pim-3 . In hepatocellular carcinoma (HCC), the oncogene CHD1L was found to drive the overexpression of TCTP, resulting in an increased number of mitotic defects (Chan et al 2012b). TCTP in turn promoted the degradation of Cdc25C during mitosis, leading to a faster mitotic exit and miss-segregation of chromosomes and consequently to chromosomal instability.…”
Section: Tctp a Microtubule Stabilising Protein At The Mitotic And Tmentioning
confidence: 99%
See 2 more Smart Citations